A neutron scattering perspective on the structure, softness and dynamics of the ligand shell of PbS nanocrystals in solution. Issue 33 (13th August 2020) - Seydel, Tilo; Koza, Michael Marek; Matsarskaia, Olga; André, Alexander; Maiti, Santanu; Weber, Michelle; Schweins, Ralf; Prévost, Sylvain; Schreiber, Frank; Scheele, Marcus
Abstract : Time-averaged and energy-resolved neutron and X-ray scattering reveal the structure of the ligand shell, temperature-dependent diffusion and the phonon spectrum of PbS nanocrystals functionalized with oleic acid in solution. Abstract : Small-angle neutron and X-ray scattering, neutron backscattering and neutron time-of-flight spectroscopy are applied to reveal the structure of the ligand shell, the temperature-dependent diffusion properties and the phonon spectrum of PbS nanocrystals functionalized with oleic acid in deuterated hexane. The nanocrystals decorated with oleic acid as well as the desorbed ligand molecules exhibit simple Brownian diffusion with a Stokes–Einstein temperature-dependence and inhibited freezing. Ligand molecules desorbed from the surface show strong spatial confinement. The phonon spectrum of oleic acid adsorbed to the nanocrystal surface exhibits hybrid modes with a predominant Pb-character. Low-energy surface modes of the NCs are prominent and indicate a large mechanical softness in solution. This work provides comprehensive insights into the ligand–particle interaction of colloidal nanocrystals in solution and highlights its effect on the diffusion and vibrational properties as well as their mechanical softness.